Polymorphs of the Gadolinite‐Type Borates ZrB2O5 and HfB2O5 Under Extreme Pressure. Issue 19 (3rd March 2021) - Pakhomova, Anna; Fuchs, Birgit; Dubrovinsky, Leonid S.; Dubrovinskaia, Natalia; Huppertz, Hubert
Abstract: Based on the results from previous high‐pressure experiments on the gadolinite‐type mineral datolite, CaBSiO4 (OH), the behavior of the isostructural borates β ‐HfB2 O5 and β ‐ZrB2 O5 have been studied by synchrotron‐based in situ high‐pressure single‐crystal X‐ray diffraction experiments. On compression to 120 GPa, both borate layer‐structures are preserved. Additionally, at ≈114 GPa, the formation of a second phase can be observed in both compounds. The new high‐pressure modification γ ‐ZrB2 O5 features a rearrangement of the corner‐sharing BO4 tetrahedra, while still maintaining the four‐ and eight‐membered rings. The new phase γ ‐HfB2 O5 contains ten‐membered rings including the rare structural motif of edge‐sharing BO4 tetrahedra with exceptionally short B−O and B⋅⋅⋅B distances. For both structures, unusually high coordination numbers are found for the transition metal cations, with ninefold coordinated Hf 4+, and tenfold coordinated Zr 4+, respectively. These findings remarkably show the potential of cold compression as a low‐energy pathway to discover metastable structures that exhibit new coordinations and structural motifs. Abstract : Push the boundaries : The behavior of β ‐HfB2 O5 and β ‐ZrB2 O5 under extreme pressure up to 120 GPa has been studied by synchrotron‐based in situ high‐pressure X‐ray diffraction in a diamond anvil cell. Both compounds remain stable to the highest applied pressure and for both experiments, a second additional phase, named γ ‐HfB2 O5 and γ ‐ZrB2 O5, respectively, was found at pressures above 114 GPa.